Novel recombinant porcine enterovirus G viruses lacking structural proteins are maintained in pig farms in Japan - MASUDA, Tsuneyuki; BORJIGIN, Sumiya; NAGAI, Makoto; MAKINO, Shinji; MIZUTANI, Tetsuya; MATSUMURA, Hirofumi; OZAWA, Takuji; OBA, Mami; RONGDUO, Wen; IMAI, Ryo; KAIXIN, Li (Journal of Veterinary Medical Science, 2023)
Type 1 recombinant enterovirus G (EV-G), which carries the papain-like cysteine protease (PLCP) gene of torovirus between its 2C/3A regions, and type 2 recombinant EV-G, which carries the torovirus PLCP gene with its flanking regions having non-EV-G sequences in place of the viral structural genes, have been detected in pig farms in several countries. In a previous study, we collected 222 fecal samples from 77 pig farms from 2104 to 2016 and detected one type 2 recombinant EV-G genome by metagenomics sequencing. In this study, we reanalyzed the metagenomic data and detected 11 type 2 recombinant EV-G genomes. In addition, we discovered new type 2 recombinant EV-G genomes of the two strains from two pig farms samples in 2018 and 2019. Thus, we identified the genomes of 13 novel type 2 recombinant EV-Gs isolated from several pig farms in Japan. Type 2 recombinant EV-G has previously been detected only in neonatal piglets. The present findings suggest that type 2 recombinant EV-G replicates in weaning piglets and sows. The detection of type 1 recombinant EV-Gs and type 2 recombinant EV-Gs at 3-year and 2-year intervals, respectively, from the same pig farm suggests that the viruses were persistently infecting or circulating in these farms.